2015
DOI: 10.1038/srep14799
|View full text |Cite
|
Sign up to set email alerts
|

Drought susceptibility of modern rice varieties: an effect of linkage of drought tolerance with undesirable traits

Abstract: Green Revolution (GR) rice varieties are high yielding but typically drought sensitive. This is partly due to the tight linkage between the loci governing plant height and drought tolerance. This linkage is illustrated here through characterization of qDTY1.1, a QTL for grain yield under drought that co-segregates with the GR gene sd1 for semi-dwarf plant height. We report that the loss of the qDTY1.1 allele during the GR was due to its tight linkage in repulsion with the sd1 allele. Other drought-yield QTLs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 56 publications
6
118
3
Order By: Relevance
“…Similarly, other QTLs like qDTY 1.1 have been reported to show linkage with other undesirable (Vikram et al 2015). The reduction of some of the progenies under non-stress in the present study indicates the existence of similar undesirable linkages for qDTY 3.2 .…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, other QTLs like qDTY 1.1 have been reported to show linkage with other undesirable (Vikram et al 2015). The reduction of some of the progenies under non-stress in the present study indicates the existence of similar undesirable linkages for qDTY 3.2 .…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, it is possible that the tradeoff in high yield potential among genotypes showing the greatest degree of root architectural plasticity may be due to genetic linkage rather than functional tradeoffs. Unfavorable linkages between high yield under drought and undesirable traits such as tall plant height and very early flowering have been reported previously, and the linkages were successfully broken through breeding to develop high-yielding, medium-duration drought-tolerant rice varieties (Swamy et al, 2013;Vikram et al, 2015). If this is the case in our study, such undesirable linkages could be broken through precise identification and fine-mapping of the genomic regions governing the root plasticity traits identified here.…”
Section: Discussionmentioning
confidence: 82%
“…The effectiveness of this approach using just 20 genotypes per population in the field studies is evidenced by the identification of a locus for grain yield at the same locus on chromosome 10 as a QTL for grain yield reported by Sandhu et al (2015) from a population of 300 genotypes. In terms of plasticity, the region on chromosome 1 (loci id1023892 and id1024972) is located near qDTY 1.1 , a major-effect drought-yield QTL that has been observed to confer plastic responses to drought, including increased root growth at depth and regulation of shoot growth (Vikram et al, 2015), as well as a hot spot for root traits including an increased proportion of deep roots by drought in the OryzaSNP panel (Wade et al, 2015). No plasticity traits from this study were colocated with the recently identified QTL qLLRN-12 for plasticity in lateral root growth under soil moisture fluctuation stress (Niones et al, 2015), although a locus at which root traits were detected in the Aus 276 population (id12001321 on chromosome 12) colocates with qLLRN-12.…”
Section: Discussionmentioning
confidence: 99%
“…Such a drought avoidance strategy may enable rice to enhance survival by postponing blossoming until the upcoming rainy season. Although most rice cultivars tend to delay flowering under drought stress conditions, acceleration of flowering under drought conditions has also been documented in some modern rice varieties (Xu et al, 2005;Vikram et al, 2015). These examples demonstrate the complexity and diversity of rice genotype-environment interactions as a result of domestication.…”
Section: Discussion Drought Inhibition Of Flowering a Rice Unique Drmentioning
confidence: 99%